Granulocyte-Macrophage Colony Stimulating Factor in Single Blastocyst Conditioned Medium as a Biomarker for Predicting Implantation Outcome of Embryo - Chen, Peilin; Huang, Chunyu; Sun, Qing; Zhong, Huixian; Xiong, Feng; Liu, Su; Yao, Zhihong; Liu, Zhiqiang; Wan, Caiyun; Zeng, Yong; Diao, Lianghui (Frontiers in Immunology, 2021)
Background: It is highly desirable to develop new strategies based on secret omics to more accurately selection of embryos with the highest developmental potential for transfer. Granulocyte-macrophage colony-stimulating factor (GM-CSF) has been reported to promote embryo development and pregnancy establishment. However, the predictive value of GM-CSF in single blastocyst selection remains unclear. This study is to determine the concentration of granulocyte-macrophage colony-stimulating factor (GM-CSF) in human single-blastocyst conditioned medium (SBCM) and to evaluate its association with embryo quality and pregnancy outcome. Methods: This study included patients with ≤38 years of age receiving the first cycle of assisted reproductive therapy with the number of top-quality embryos formed by the fertilized two pronuclear zygotes on day 3≥4. A total of 126 SBCM samples (SBCMs) were included, of which 77 were from frozen-thawed single blastocyst transfer cycles (FET-SBCMs). The concentrations of GM-CSF were detected and analyzed for their possible association with embryo quality and pregnancy outcomes. The top-quality embryo (TQ), positive HCG (HP), clinical pregnancy (CP), and ongoing pregnancy (OP) rates were determined and compared based on GM-CSF concentrations. Results: The detection rate of GM-CSF was found to be 50% in all SBCMs. There were significant differences in TQ rate, HP rate, CP rate and OP rate among high concentration group, medium concentration group and low concentration group. Both GM-CSF alone or GM-CSF combined with the morphological score (MS) had a greater AUC of ROC curve than that of MS alone to predict the pregnancy outcome, and GM-CSF combined with MS had the highest AUC. Conclusions: The concentration of GM-CSF in SBCM was detected at fg/mL levels, which was associated with embryo quality and pregnancy outcome. Collectively, GM-CSF may be used as a biomarker for prediction of pregnancy outcome and selection of embryos with high developmental potential for transfer in ART.